A comparative study on folk sports inheritance in China and South Korea: Influencing factors and mediating roles - Xiaobin Jin; Yu Hou (PLoS ONE, 2025)
This study investigates the similarities and differences in the factors influencing folk sports inheritance in China and South Korea, providing a theoretical foundation for fostering bilateral learning and collaboration in this field. The research employs a five-dimensional framework—Inheritance Subject, Inheritance Object, Inheritance Intermediary, Inheritance Environment, and Inheritance Effect—comprising 32 observed variables. Surveys were conducted among 336 Chinese and 331 Korean folk sports participants, organizers, and researchers, with data analyzed using SPSS and AMOS software. The findings indicate a consistent influence of these dimensions on folk sports inheritance in both countries. Specifically, the Inheritance Object, Inheritance Intermediary, and Inheritance Environment positively affect the Inheritance Subject, which, in turn, directly enhances the Inheritance Effect. Furthermore, the Inheritance Subject plays a crucial mediating role within the inheritance system, linking the Inheritance Object, Inheritance Intermediary, and Inheritance Environment while facilitating the realization of the Inheritance Effect. Despite these shared structural influences, notable differences exist in the inheritance processes of folk sports in China and South Korea. South Korea demonstrates strengths in recognizing and cultivating inheritors, establishing institutional frameworks, and developing a sustainable inheritance ecosystem, whereas Chinese folk sports inheritors exhibit superior technical proficiency. This study contributes to the theoretical discourse on folk sports inheritance by highlighting the mediating role of the Inheritance Subject and offering strategic insights for sustaining folk sports traditions in both countries.